2007
DOI: 10.1063/1.2777142
|View full text |Cite
|
Sign up to set email alerts
|

Hg + Br → Hg Br recombination and collision-induced dissociation dynamics

Abstract: A global potential energy surface has been constructed for the system HgBr+Ar-->Hg+Br+Ar to determine temperature dependent rate constants for the collision-induced dissociation (CID) and recombination of Hg and Br atoms. The surface was decomposed using a many-body expansion. Accurate two-body potentials for HgBr, HgAr, and ArBr were calculated using coupled cluster theory with single and double excitations and a perturbative treatment of triple excitations [CCSD(T)], as well as the multireference averaged co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 64 publications
3
50
0
Order By: Relevance
“…b) Ozone mixing ratio in the atmosphere (35 cm above the surface) and in the air of snow obtained at Alert, Canada (828N) from February 29th to March 9th during twilight conditions. The same decreasing trend can be observed before (10-28 February) and after (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) March) this period. Data are extracted from ref.…”
Section: àsupporting
confidence: 76%
See 1 more Smart Citation
“…b) Ozone mixing ratio in the atmosphere (35 cm above the surface) and in the air of snow obtained at Alert, Canada (828N) from February 29th to March 9th during twilight conditions. The same decreasing trend can be observed before (10-28 February) and after (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) March) this period. Data are extracted from ref.…”
Section: àsupporting
confidence: 76%
“…[18][19][20][21][22] However, Tossel [23] reported a theoretical investigation of the thermal formation of Hg II complexes in the presence of various radicals. Balabanov et al [24][25][26] also reported dynamical studies on the collision of mercury atoms with halogen molecules. Theoretical methods, and in particular DFT methods, have proven in the past their ability in predicting the reactivity of metallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous laboratory studies reported apparent rate coefficients in the range of (3.6 ± 0.9) × 10 −13 to (3.2 ± 0.3) × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [19,20,22]. Theoretical studies estimated the rate constants to be from 9.8 × 10 −13 to 2.1 × 10 −12 cm 3 molec −1 s −1 , at 1 atm and 298 K [3,21,23]. Theoretical and experimental rate constants for mercury oxidation by Br and Cl atoms at 298 K have previously been compared in detail in Table A.2 by Subir et al [18].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 99%
“…There have been several quantum chemical studies of mercury compounds, [18,19, where those of the Peterson group [18,[21][22][23][24][25][26][27][28] and those by Tossell [29][30][31][32][33] are most noteworthy. Each of these investigations focused on selected mercury compounds HgX; however none of them attempted a comprehensive study of mercury bonding by varying X systematically within the periodic table.…”
Section: Bdea C H T U N G T R E N N U N G (Hgx)àbdea C H T U N G T R mentioning
confidence: 99%
“…However this reaction sequence can be excluded on the basis of theoretical calculations carried out herein and in the studies of others. [18][19][20][21][22][23][24][25][26][27][28][29][30] The reaction of elemental Hg with OH radicals is more likely considering a reaction energy of 12 kcal mol…”
mentioning
confidence: 99%